Hydrophobic agglomeration flotation of oxidized digenite fine particles induced by Na2S and butyl xanthate. (1st July 2021) - Xue, Jiwei; Ren, Dawei; Chen, Tong; Bu, Xianzhong; Wan, He; Song, Zhenguo; Zhao, Chen
Graphical abstract: Highlights: The recovery of heavily oxidized digenite fine particles is of great significance. The effect of Na2 S and SBX on the flotation of oxidized digenite fine particles was investigated. The hydrophobic agglomeration of oxidized digenite fine particles could be induced by Na2 S and SBX. Na2 S and SBX could effectively restore the floatability of heavily oxidized digentie fine particles. Findings can help understanding the hydrophobic agglomeration mechanism of oxidized digenite fine particles. Abstract: Secondary copper sulfide mineral fine particles are easily oxidized, and their effective recovery by froth flotation is extremely challenging. This study investigated the roles of sodium sulfide (Na2 S) and sodium butyl xanthate (SBX) in the hydrophobic agglomeration flotation of oxidized digenite fine particles. The microflotation experiments of the study showed that the simultaneous addition of Na2 S and SBX is beneficial for improving the floatability of heavily oxidized digenite fine particles. In addition, the recovery at pH 7.0 was apparently higher than that of the unoxidized digenite fine particles, indicating that hydrophobic agglomeration of digenite fine particles may occur. The results of the zeta potential measurements, X-ray photoelectron spectroscopy analyses, and contact angle measurements suggested that negatively charged hydrogen sulfide ion and xanthate ion respectively hydrolyzed from Na2 S and SBX adsorbed on the surface of digenite. Moreover, they significantly decrease the amount of hydrophilic copper sulfate and oxides/hydroxides on the surface, thus improving the surface hydrophobic degree of digenite. The results of the optical microscopy analysis, particle size analysis, and extended Derjaguin–Landau–Verwey–Overbeek theory calculations provided strong evidence for the roles of Na2 S and SBX in promoting the hydrophobic agglomeration of the digenite fine particles. After treatment with Na2 S and SBX, the total interaction energies between the digenite fine particles were negative, indicating that the strong hydrophobic attractive forces promote the formation of large-sized agglomerates, enabling the digenite fine particles to be more easily captured by bubbles than those without the treatment. Therefore, effective recovery of heavily oxidized digenite fine particles can be realized by the hydrophobic agglomeration flotation technology induced by Na2 S and SBX.